RELEVANCE OF AHMAD DAHLAN'S CONCEPT OF RENEWING ISLAMIC EDUCATION TO TODAY'S EDUCATION - Suwarsih, Amelia Nia Pradipa Asih; Fitria, Gina; Arsika, Intan Dihni; Ressa, Ressa; Amrillah, Rizki (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
This study investigates the relationship between the philosophical works of KH Ahmad Dahlan and modern Islamic education. This research focuses on this question and the problems facing the modern Islamic education system, which is characterized by the need to integrate traditional Islamic teachings with contemporary educational demands. This research also examines how Dahlan's thinking can help bridge these problems. This paper interprets Dahlan's educational philosophy through analysis of historical texts and modern educational theory. This is done using a qualitative methodological approach. These results indicate that Dahlan's emphasis on critical thinking, rationality, and community involvement in education is in accordance with current educational needs. This study concludes that Dahlan's approach offers an important perspective on curriculum development and pedagogical strategies that are rooted in Islamic traditions and adapt to the needs of modern society. In a broader context, this research emphasizes the possibility of change in Islamic education that considers the spiritual and practical aspects of modern education.